Extension on Prevention and Early Treatment of Diarrhea to Children of Sekolah Dasar Negeri 006 Kota Samarinda: Penyuluhan Pencegahan dan Penatalaksanaan Awal Diare pada Anak Sekolah Dasar Negeri 006 Kota Samarinda - M. Arifuddin; Fitri Nurul Choiriyah; Amalia Pratamasari Hartini Nurul Mahmudah (Jurnal Abdita Naturafarm, 2026)
Diarrhea is a public health issue with a high incidence rate, especially among children. School-age children were a vulnerable group due to limited knowledge regarding the prevention and early management of diarrhea. This activity aimed to ensure that students at Sekolah Dasar Negeri 006 Kota Samarinda had adequate knowledge about diarrhea and were aware of the importance of prevention and early management of diarrhea. Counseling was conducted with 22 children of Sekolah Dasar Negeri 006 Kota Samarinda. The activity involved distributing leaflets, presenting materials, and demonstrating the preparation of oral rehydration salts (ORS) solution, accompanied by questionnaires. Based on the questionnaire results, 27.3% of respondents had good knowledge in the pre-test and 90.9% in the post-test with an Asymp. Sig. (2-tailed) value of 0.000 in the Wilcoxon test. Provided this education increased children's knowledge about the prevention and early management of diarrhea.